Multishape Pembelajaran Jarak Jauh di Era 5.0: Ragam Model dan Integrasi Teknologi Human-Centric (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study addresses the gap between the rapid development of diverse (multishape) distance learning models and the implementation of human-centric technology principles in the Society 5.0 era, which often results in technically driven yet psychologically isolating learning experiences. The research question guiding this study is: How can the multishape configuration of distance learning be integrated with human-centric technology principles to create effective and student-centered learning? Employing a systematic literature review method, data were collected from primary sources in the Google Scholar, Garuda, and Sinta databases (publications 2015–2025) and analyzed using thematic content analysis. The findings reveal three main outcomes: (1) the evolution of multishape models (synchronous, asynchronous, blended, flipped) supported by specific platforms; (2) the core convergence of human-centric principles—personalization, meaningful interaction, and well-being—with educational technology; and (3) a practical integrative framework for synergizing model diversity with technology through smart blending and empathetic pedagogy. The study concludes that successful distance learning in the 5.0 era hinges on designing flexible, human-centered ecosystems rather than relying on single tools or models.